2023
DOI: 10.3390/su15032313
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modelling Strategies in Sustainable Housing Construction Projects in Malaysia

Abstract: Building Information Modelling (BIM) plays a very significant role in the construction industry, especially in project management decision-making and data integration efforts during the preliminary planning and design stage. This is aligned with the National Construction Policy (NCP 2030) by the Ministry of Work Malaysia, highlighting that it is timely for the construction industry players to move towards sustainability. BIM must be implemented to ensure the smooth delivery of sustainable housing construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Liu et al [42] indicated that BIM technology is widely utilized to lower energy use in buildings, yet it faces challenges and requires enhancements for its deployment in construction refurbishment endeavors. Rahim et al [43] elucidate the adoption of BIM in Malaysian sustainable housing endeav-ors as aligning with the National Construction Policy 2030's objectives by augmenting cost efficiency and mitigating environmental detriments through sustainable construction practices. This corpus of research elucidates the revolutionary impact of BIM and BEM collaboration in transcending conventional limits of energy efficiency, sustainability, and conservation within the construction industry.…”
Section: The Benefits Of Interoperability Of Bim and Bem Technologiesmentioning
confidence: 99%
“…Liu et al [42] indicated that BIM technology is widely utilized to lower energy use in buildings, yet it faces challenges and requires enhancements for its deployment in construction refurbishment endeavors. Rahim et al [43] elucidate the adoption of BIM in Malaysian sustainable housing endeav-ors as aligning with the National Construction Policy 2030's objectives by augmenting cost efficiency and mitigating environmental detriments through sustainable construction practices. This corpus of research elucidates the revolutionary impact of BIM and BEM collaboration in transcending conventional limits of energy efficiency, sustainability, and conservation within the construction industry.…”
Section: The Benefits Of Interoperability Of Bim and Bem Technologiesmentioning
confidence: 99%